Features of distribution of titanium and silver in the internal organs of laboratory rats and mice exposed to high doses of titanium dioxide nanoparticles and its composite with nanosilver - Yavorovsky, O.P.; Andrusyshyna I.М.; Riabovol , V.M. (Medicni Perspektivi, 2023)
In Ukraine and worldwide more attention is paid to the study and application of titanium dioxide nanoparticles (TiO2 NPs). These nanoparticles find use in many industrics (medicine, cosmetology, materials science, environmental protection, etc.). The aim of the study was to study the features of the distribution of TiO2 nanoparticles, a composite of titanium nanodioxide with nanosilver (TiO2/Ag NPs) in the internal organs of laboratory animals (mice, rats) after acute intraperitoneal administration of TiO2 NPs and TiO2/Ag NPs. The objects of toxicological studies were TiO2 NPs (crystalline form - anatase, 21-28 nm in size) and TiO2/Ag NPs (17-22 nm in size, 4 wt% Ag) synthesized at the Frantsevich Institute for Problems of Materials Science NASU. Nanopowder suspensions were introduced in high doses (from 1,000 to 13,000 mg/kg) during a 14 days observation period. The content of chemical elements Ti and Ag in organs (liver, kidneys, spleen, heart, lungs, adrenal glands, thymus, brain) was determined using the method of optical emission spectroscopy with inductively coupled plasma. It was found accumulation of metals in the internal organs on the 14th observation day after a single intraperitoneal injection. It was revealed that the kidneys and liver in rats are the most sensitive to the accumulation of TiO2 and TiO2/Ag NPs; accumulation in the thymus and adrenal glands is also shown. In an experiment on mice, it was found that the kidneys, liver and spleen accumulate titanium and silver after exposure at a dose of 4, 7 and 10 thousand mg/kg of NPs of TiO2 and TiO2/Ag.